In bifurcated solution of the Cauchy problem for one class of parabolic systems - Lenуuk M. P.; Shestоpal A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1970)
Построена фундаментальная матрица решений задачи Коши для параболической системы _k=0^mA^(k)(x_1,…, x_n)^kut^k=0 в специальном римановом пространстве.